Exploring the Pharmacological Mechanisms of Xihuang Pills Against Prostate Cancer via Integrating Network Pharmacology and Experimental Validation In Vitro and In Vivo - Wu, Yongrong; You, Xujun; Lin, Qunfang; Xiong, Wei; Guo, Yinmei; Huang, Zhen; Dai, Xinjun; Chen, Zhengjia; Mei, Si; Long, Yan; Tian, Xuefei; Zhou, Qing (Frontiers in Pharmacology, 2022)
Background: Drug resistance is the major cause of increasing mortality in the prostate cancer (PCa). Therefore, it is an urgent to develop more effective therapeutic agents for the PCa treatment. Xihuang Pills (XHP) have been recorded as the efficient anti-tumor formula in the ancient Chinese medical literature which have been utilized in several types of cancers nowadays. However, the effect protective role of XHP on the PCa and its underlying mechanisms are still unclear. Methods: The active ingredients of XHP were obtained from the Traditional Chinese Medicine Systems Pharmacology Database and Analysis Platform(TCMSP) and BATMAN-TCM. The potential targets of PCa were acquired from the Gene Cards and OMIM databases. R language and Perl language program were utilized to clarify the interaction between the PCa related targets and the potential targets of XHP. The potential targets of XHP for prostate cancer were gathered from the Gene ontology and KEGG pathway. Furthermore, cell proliferation assays were verified by PC3 and LNCaP cells. The efficacy and potential mechanisms tests were confirmed by the PCa PC3 cells and mice subcutaneous transplantation. The effects of PI3K/Akt/mTOR-related proteins on proliferation, apoptosis, and cell cycle of PCa cells were measured by the CCK8, TUNEL assay, QRT-PCRand WB, respectively. Results: The active components of four traditional Chinese medicine in XHP were searched on the TCMSP and Batman TCM database. The biological active components of XHP were obtained as the OB ≥ 30% and DL ≥ 0.18 . The analysis of gene ontology and KEGG pathway identified the PI3K/Akt/mTOR signaling pathway as the XHP-associated pathway . Collectively, the results of experiments showed that XHP had the effect of inhibiting on the proliferation of PC3 and LNCaP cells. XHP promoted the apoptosis, restrained the cell cycle and invasion of the PC3 cells and subcutaneous transplantation. Meanwhile, the suppression of XHP on the level of expression of PI3K, Akt and mTOR- pathway-related pathway proteins has been identified in a dose dependent manner. Conclusion: PI3K/Akt/mTOR pathway related pathway proteins were confirmed as the potential XHP-associated targets for the PCa. XHP can suppress the proliferation of prostate cancer via inhibitions of PI3K/Akt/mTOR pathway.